Níveis de isoleucina digestível para suínos machos castrados dos 15 aos 30 kg - Lazzeri, Doglas Batista (2011)
Aiming to determine the digestible isoleucine requirement for barrows from 15 to 30 kg, two experiments were conducted, being one of digestibility and another of performance. Ten crossbreed barrows with average initial weight of 15.00 ± 0.27 kg were used to determine the ileal digestibility coefficient of amino acids from basal diet. The animals were housed individually in metabolic cages in a completely randomized design, with two treatments, five replicates and one animal per experimental unit. The treatments consisted of a basal diet with 14.13% crude protein and 0.45% isoleucine, and a free protein diet. Forty crossbreed barrows with average initial weight of 15.00 ± 0.87 kg were used to determine the digestible isoleucine requirement. The animals were distributed in a randomized block design with five treatments (0.45, 0.52, 0.59, 0.66 and 0.73% digestible isoleucine), four replicates and two animals per experimental unit. The coefficients of true ileal digestibility of essential amino acids were higher than the coefficients of apparent ileal digestibility and threonine, methionine+cystine and valine had the biggest increases. The true ileal digestibility of basal diet for lysine, threonine and tryptophan were higher than the true ileal digestible calculated amino acids. The same was not observed for true ileal digestibility of basal diet of arginine, histidine, isoleucine, leucine, methionine, methionine+cystine, phenylalanine and valine. The protein deposition rate had a quadratic effect (P<0.05) which the level of 0.600% digestible isoleucine had the highest protein deposition in carcasses of pigs. The daily isoleucine intake had quadratic effect (P<0.01), which level of 0.938% digestible isoleucine provided the higher intake. There was linear effect (P<0.01) on efficiency of isoleucine utilization for weight gain, with reduction on values of EIleUWG as levels of digestible isoleucine increased in rations. A quadratic effect (P=0.09) of digestible isoleucine levels on the final weight was observed, with better values for the level 0.599%. The level of 0.60% digestible isoleucine obtained in the present work provided a digestible isoleucine:lysine relation of 0.60. The daily requirement of digestible isoleucine was 5.86 g/day, providing 1.76g of digestible isoleucine/Mcal of metabolizable energy